Student’s Perception and Attitudes toward Public Health Profession and National Competency Examination - Lafi Munira; Lina Handayani (Intelektual Pustaka Media Utama, 2014)
One form of quality assurance is convening public health’s national competencies examination in academic phase which is conducted before students graduate from university. The purpose of this study was to determine students’s perceptions and attitudes about public health’s profession and national competencies examination. The design of this study was descriptive qualitative employed case study approach. Focus group discussion was used to collect data. Data were analyzed by content analysis. Students felt less confident about their identity profession so that requires motivation by lecturer. Students expressed the need to improve public health graduates’s competencies since academic phase. National competencies examination is important to do as a solution to guarantee the graduates’s quality. Implementation of the competencies test is need to consider aspects of management and technical readiness. National competencies examination is a tool that could proves the identity of public health graduates’s competencies. Everyone with a public health background should know that there will be a competency test then they should have an adequate preparation.